Reference material : land laws in Papua New Guinea. - Papua New Guinea University of Technology (Papua New Guinea University of Technology, 2003)
Content: Land Act 1996. - - Physical Planning Act 1989. - - Survey Act 1969. - - Valuation Act 1967. - - Land Groups Incorporated Act 1974. - - Land Disputes Settlement Act 1975. - - Environmental Planning Act 1978. - - Water Resources Act 1982.